Contributions of respiratory rehabilitation to clinical practice in a pandemic. A reflection - Sérgio Vaz; Ana Loureiro; Andreia Félix; André Novo (Associação Portuguesa dos Enfermeiros de Reabilitação, 2021)
Introduction: The assistance activity of respiratory rehabilitation was, in most countries, interrupted due to the pandemic caused by COVID-19. COVID-19 is a multisystem disease that can progress to acute respiratory failure syndrome, which can lead to serious sequelae. It is estimated that the survivors' sequelae could dominate clinical practice for years to come. Objective: To identify the main contributions to clinical practice in Respiratory Telerehabilitation in Pandemic. Methodology: Critical-reflective methodology, in which contributions from selected articles. Reflection Development: Starting early the post-hospital rehabilitation, before patients develop severe or limited ventilatory incapacity, is extremely important. Respiratory rehabilitation is an ongoing iterative process that requires frequent monitoring of the patient's functional capacity, used to guide and adjust treatment and care based on their progress. Its objectives are to reduce complications, minimize disability, preserve functionality, improve symptoms of dyspnea, anxiety, depression and improve quality of life. Telehealth and Telerehabilitation can be essential tools in providing care to these people. Conclusion: Telehealth and Telerehabilitation as digital practice tools can be fundamental allies in the implementation of respiratory rehabilitation programs, not only in times of suspension of in-person care activities, but also in order to improve access to differentiated health care and management of health resources.